Analisis Deret Vokal dan Deret Konsonan Pada Puisi “Krawang Bekasi” Karya Chiril Anwar - Mirabella Husen Assegaf; Feby Aulia Trihapsari; Salwa Rachmadini (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
The poem "Karawang Bekasi" has the potential to line up with other vocals. However, from the data obtained, no vowel series were found /a.e/, /a.o/, /i.u/, /i.e/, /i.o/, /u.a/, /u.i/, /u.e/, /u.o/, /e.a/, /e.i/, /e.o/, /e.u/, /o.a/, /o.i/, /o.e/, and /o.u/. Furthermore, from these data, it can also be seen that the consonant series found in the poem "Karawang Bekasi" is the 'n' consonant series which is lined up with the 'g' consonant. The least number of consonant series is the consonant series: /g.g/, /g.k/, /g.l/, /h.r/, /k.r/, /m.d/, /n.d/, /n.j/, /n.m/, /r.d/, /r.d/, /r.k/, /r.n/, /r.s/, /r.t/, /t.t/, /u.s/. This study examines the phonemic phonotatic structure in vowel series and consonant series in Tunjung language. The approach used in this study is qualitative descriptive. The purpose of this study is so that readers can explore the deep phonetic and aesthetic dimensions in literary works, providing a richer understanding of the poet's techniques and the meanings contained in the poem. The method taken is a qualitative descriptive method. The results of this analysis are expected to contribute to a further understanding of how vowel and consonant sequences become important instruments in designing sound structure and meaning in poetry. In addition, this research can enrich the perspectives of readers and researchers on the linguistic and artistic dynamics contained in literary works, especially in the context of the Krawang Bekasi poem.